2015
DOI: 10.1089/mdr.2014.0076
|View full text |Cite
|
Sign up to set email alerts
|

Dominance of Multidrug-Resistant Denmark14-32 (ST230) Clone AmongStreptococcus pneumoniaeSerotype 19A Isolates Causing Pneumococcal Disease in Bulgaria from 1992 to 2013

Abstract: A pneumococcal conjugate vaccine (PCV10) was introduced in Bulgarian national immunization program since April 2010. Clonal composition based on pulsed-field gel electrophoresis and multilocus sequence typing genotyping of 52 serotype 19A Streptococcus pneumoniae isolates was analyzed. These were invasive and respiratory isolates collected between 1992 and 2013 from both children (78.8% <5 years) and adults with pneumococcal infections. Multidrug resistance was found in 82.7% of all 19A isolates. The most prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…These lineages related to major international clones that have different distributions over the world. CC156 has a minor representation among serotype 19A pneumococci, and this has not changed significantly under PCV pressure [6, 7, 13, 18, 21]. The same was true for the PMEN clone Colombia 23F -26, to which our ST663 clonal group was attributed by the eBURST analysis [6, 18].…”
Section: Discussionmentioning
confidence: 78%
“…These lineages related to major international clones that have different distributions over the world. CC156 has a minor representation among serotype 19A pneumococci, and this has not changed significantly under PCV pressure [6, 7, 13, 18, 21]. The same was true for the PMEN clone Colombia 23F -26, to which our ST663 clonal group was attributed by the eBURST analysis [6, 18].…”
Section: Discussionmentioning
confidence: 78%
“…Also interesting, serotype 24F was the second most common serotype in children less than 2 years old during the study period when analyzing the results by age groups. The major clone detected in serotype 24F was ST230, a multidrug resistant clone related with the increase of serotype 19A in Bulgaria, Portugal and in our geographical area [ 29 , 31 , 32 ]. A previous study conducted in our area also observed an increase in the rate of serotype 24 several years after PCV7 introduction associated with the clonal expansion of this genotype [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Serotype 19A has been recognized as a multidrug-resistant type in the United States [22] , [23] , [24] and Europe during the PCV7 era [25] , [26] . Also in Japan, as demonstrated in the present study, serotype 19A emerged as a dominant serotype after PCV7 introduction, showing the highest rate of isolates with both erm (B) and mef (A/E) among all the serotypes.…”
Section: Discussionmentioning
confidence: 99%